Tanggapan Pemustaka Terhadap Desain Interior (Studi Deskriptif di Dinas Perpustakaan dan Kearsipan Kabupaten Tanah Laut Kalimantan Selatan) - Mahmudah, Ismah; Juairiah, Juairiah; Andini, Yokke (Librarianship in Muslim Societies, 2023)
The design of the Tanah Laut Regency Library and Archives Service building looks attractive in terms of its artistic and modern design. However, addressing interior design problems is still necessary because they cause inconvenience to visiting users. Therefore, it is necessary to view the interior design of the Tanah Laut Regency Library and Archives Service from the perceptions or responses of users. The type of research used is descriptive research with quantitative methods. The research population is 432 users. Determination of the sample in this study using the Slovin formula with an error rate of 10% obtained sample of 82 respondents. The study's results by distributing questionnaires showed that users' responses to interior design at the Tanah Laut District Library and Archives Service could be identified based on indicators of interior design elements. The user's response to spatial planning, color, and air circulation has an average score of 3.73, 3.97, and 3.44, which are in the agreed category. The user's response to lighting and spatial planning elements averaged 2.96, and 2.91 was in the quite agree category. Even though the overall average score of 3.49 is in the agreed category for lighting and spatial planning, it needs to be improved again because it is still in the entirely agreed category, which shows that there is still some inconvenience for users to be in the library.